2021
DOI: 10.3389/fpls.2021.693044
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal-Assisted Phytoremediation and Intercropping Strategies Improved the Health of Contaminated Soil in a Peri-Urban Area

Abstract: Soils of abandoned and vacant lands in the periphery of cities are frequently subjected to illegal dumping and can undergo degradation processes such as depletion of organic matter and nutrients, reduced biodiversity, and the presence of contaminants, which may exert an intense abiotic stress on biological communities. Mycorrhizal-assisted phytoremediation and intercropping strategies are highly suitable options for remediation of these sites. A two-year field experiment was conducted at a peri-urban site cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 89 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…In other studies with L. perenne, it has been found that its roots form arbuscular-type mycorrhizae (Leudo et al 2020), which, according to some authors, makes them unique model systems for the study of interactions between plants and microorganisms (Gómez-Sagasti et al 2021). In this study, it has been proven that mycorrhizae favor the presence of other microorganisms that help in the performance of metal uptake by the roots.…”
Section: Difference In the Microbial Communitymentioning
confidence: 57%
“…In other studies with L. perenne, it has been found that its roots form arbuscular-type mycorrhizae (Leudo et al 2020), which, according to some authors, makes them unique model systems for the study of interactions between plants and microorganisms (Gómez-Sagasti et al 2021). In this study, it has been proven that mycorrhizae favor the presence of other microorganisms that help in the performance of metal uptake by the roots.…”
Section: Difference In the Microbial Communitymentioning
confidence: 57%
“…In addition, Plants can directly alter the soil microbiome by secreting and releasing bioactive molecules and metabolites ( Pang et al, 2021 ). Root exudates may differ between plant species, different growth stages, and even between the same plant species ( Micallef et al, 2009 ; Li et al, 2013 ; Dietz et al, 2019 ), therefore, root exudates from the twelve alfalfa cultivars might have led to changes in soil physiochemical properties ( Zhang et al, 2020 ), and most likely contributed to the effects on soil microbial activity and biomass ( Gomez-Sagasti et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned reductions were probably influenced by plant growth that improves rhizosphere interactions by releasing root exudates. These interactions help to create a suitable environment for microbial development, increasing rhizodegradation and microbial degradation processes (Reilley et al, 1996;Epelde et al, 2009;Stefanowicz et al, 2012;Nui et al, 2021;Gómez-Sagasti et al, 2021). Different authors (Park et al, 2011;Niu et al, 2021) have already reported that plants can influence metal uptake and/or immobilization through different interactions in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%